A core-shell structure perovskite catalyst containing amorphous boron-oxygen layer and preparation and application thereof
Patent Information
- Application Number
- CN202610379190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-26
- Publication Date
- 2026-06-23
Smart Images

Figure CN122252168A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalytic materials technology, specifically relating to a core-shell perovskite catalyst for the oxidative dehydrogenation (ODHP) of propane to propylene, its preparation method, and its application. More specifically, this invention provides a composite catalyst with a crystalline perovskite core and an amorphous borate shell, characterized by a simple, low-cost, and reproducible preparation process. This catalyst exhibits high activity, high selectivity, and excellent long-term stability in the propane ODHP reaction, demonstrating significant potential for industrial applications. Background Technology
[0002] Propylene is a key chemical platform molecule, with a global annual demand exceeding 100 million tons, mainly used to produce high-value-added products such as polypropylene, acrylonitrile, and propylene oxide. Currently, industrial propylene production primarily relies on petroleum-based routes, such as steam cracking and catalytic cracking (FCC). These processes are energy-intensive, generate significant carbon emissions, and depend on fossil resources. While direct propane dehydrogenation (PDH) is a simpler route, it is limited by thermodynamic equilibrium and requires high temperatures (>550°C). The catalyst is prone to coking and deactivation during the reaction, hindering its long-term operation. Oxidative propane dehydrogenation (ODHP), on the other hand, is an exothermic process, not subject to equilibrium constraints, and can achieve high conversion rates at lower temperatures while significantly suppressing coking formation. It is considered a highly promising alternative route for propylene production.
[0003] In recent years, non-metallic boron-based catalysts (such as hexagonal boron nitride (h-BN) and supported boron oxides) have shown high olefin selectivity in ODHP, attracting widespread attention. The high selectivity of boron-based catalysts stems from the unique electronic structure of boron species, which can activate alkane CH bonds through surface radical mechanisms and inhibit over-oxidation. However, these catalysts face serious stability challenges in practical applications: active boron species (especially B₂O₃) are prone to volatilization, migration, or reaction with moisture to form volatile boric acids at reaction temperatures (≈500℃), leading to a rapid decline in activity. Although studies have attempted to stabilize boron centers through strategies such as support regulation and the construction of boron-oxygen networks, how to completely solve the boron loss problem while maintaining high activity remains a critical technical bottleneck that urgently needs to be overcome in this field.
[0004] To address the aforementioned problems, this invention proposes a novel catalyst structure design strategy: using crystalline perovskite (such as LaAlO3) as the core support, and constructing an amorphous borate (LaAlBO3) layer in situ on its surface through heat treatment. x A capping layer is formed to create a composite catalyst with a clearly defined core-shell interface. x(B@LAO). In this structure, the shell is tightly bound to the support via strong covalent MOB bonds (M being metals such as La and Al in perovskite), thus firmly anchoring the active boron species and effectively suppressing their high-temperature volatilization. Experimental results show that after continuous operation at 500℃ for 100 hours, this catalyst still maintains approximately 24% propane conversion and over 97% total olefin selectivity, with extremely low boron loss. This structural design and stability performance are unprecedented among currently reported ODHP boron-based catalysts, providing an innovative approach for developing ODHP catalysts that combine high activity, high selectivity, and long lifetime. Summary of the Invention
[0005] The present invention aims to provide a core-shell perovskite catalyst for the oxidative dehydrogenation of propane to propylene, its preparation method, and its application. This catalyst has a stable structure and robust active sites, and its preparation process is simple and reproducible. It effectively solves the key problems of easy volatility and poor stability of active components in traditional boron-based catalysts, exhibiting high activity, high selectivity, and excellent long-term operational stability in the propane oxidative dehydrogenation reaction.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: One of the objectives of this invention is to protect a core-shell perovskite catalyst containing an amorphous boron oxide layer, which consists of a crystalline perovskite support and an amorphous borate layer covering the surface of the support, forming a core-shell structure.
[0007] Further, the perovskite support is an ABO3 type perovskite, wherein A is selected from at least one of La, Sm, and Ce, and B is selected from at least one of Al, Co, Ni, Mn, and Fe. Preferably, the perovskite support is LaAlO3 or SmAlO3.
[0008] Furthermore, the amorphous borate layer is tightly bonded to the perovskite support through a bonding structure with the structural formula MOB, wherein M is selected from at least one of the metal cations such as La and Al in the perovskite support.
[0009] Furthermore, the thickness of the amorphous borate layer is 0.5 nm to 5 nm.
[0010] Furthermore, based on the total mass of the catalyst, the mass content of boron is 5% to 50%, preferably 15% to 50%.
[0011] A second objective of this invention is to protect the preparation method of the core-shell structured perovskite catalyst, which includes the following steps: (1) Preparation of perovskite support; (2) The perovskite support and the boron source were mixed to obtain a mixture; (3) The mixture obtained in step (2) is heat-treated so that the boron species react with the perovskite surface to form an amorphous borate layer in situ.
[0012] Further, the boron source in step (2) is selected from at least one of boric acid, boron oxide, and borate esters, preferably boric acid.
[0013] Furthermore, in step (2), the perovskite support and the boron source are mixed by solution impregnation or solid-phase grinding.
[0014] Furthermore, the atmosphere for the heat treatment in step (3) is nitrogen, argon, or a mixture thereof.
[0015] Furthermore, the heat treatment temperature in step (3) is 400 ℃~600 ℃, preferably 450 ℃~550 ℃, and the time is 1~3 hours.
[0016] The third objective of this invention is to protect the application of the core-shell perovskite catalyst in the catalytic oxidative dehydrogenation reaction of alkanes, specifically by using the core-shell perovskite catalyst to catalyze the oxidative dehydrogenation of propane to produce propylene.
[0017] Furthermore, the temperature of the oxidative dehydrogenation reaction is 480 ℃~520 ℃, the reaction time is 0.5 h~2 h, and the volume ratio of C3H8 to O2 in the reaction feed gas is 1:1~3:1.
[0018] The beneficial effects of this invention are as follows: 1. Stable structure and robust active sites: Active boron species are anchored to the perovskite surface through strong covalent bonds formed in situ via MOB, which significantly inhibits boron volatilization and loss at high temperatures, solving the core problems of poor stability and limited service life of traditional supported boron catalysts.
[0019] 2. Simple preparation process and controllable cost: The preparation method is based on common impregnation and heat treatment processes, requiring no complex equipment or templates, and has high reproducibility. The perovskite support used can be synthesized through conventional sol-gel methods, and the boron source is inexpensive and readily available.
[0020] 3. Excellent catalytic performance: This catalyst exhibits both high activity and high selectivity in the propane oxidative dehydrogenation reaction. For example, after continuous operation at 500°C for 100 hours, the propane conversion rate can be stably maintained at approximately 24%, and the total olefin selectivity remains above 97%.
[0021] 4. Broad application prospects: The catalyst design strategy is highly universal, and its performance can be further optimized by adjusting the perovskite composition and boron loading. It provides a new approach for developing efficient, stable, and economical alkane dehydrogenation catalysts and has significant potential for industrial application. Attached Figure Description
[0022] Figure 1 The image shows a scanning electron microscope (SEM) image of the core-shell structured catalyst 37B@LAO prepared in Example 1.
[0023] Figure 2 High-angle annular dark-field scanning transmission electron microscope (HAADF-TEM) image of the core-shell structured catalyst 37B@LAO prepared in Example 1.
[0024] Figure 3 The high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image of the core-shell structure catalyst 37B@LAO prepared in Example 1, the corresponding electron energy loss spectrum (EELS) elemental analysis, and its dynamic evolution under ODHP reaction are shown.
[0025] Figure 4 Fourier transform infrared (FT-IR) spectra of the core-shell catalyst 37B@LAO prepared in Example 1 before and after the ODHP reaction.
[0026] Figure 5 For different boron loading x X-ray powder diffraction (XRD) pattern of the B@LAO sample.
[0027] Figure 6 This is a comparison chart of the catalytic performance of different catalysts in the oxidative dehydrogenation reaction of propane.
[0028] Figure 7 The catalytic performance of the core-shell structured catalyst 37B@LAO prepared in Example 1 in the propane oxidative dehydrogenation reaction at different temperatures is shown in the figure.
[0029] Figure 8 The graph shows the long-term stability of the core-shell catalyst 37B@LAO prepared in Example 1 during continuous operation for 100 hours in the propane oxidative dehydrogenation reaction. Detailed Implementation
[0030] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.
[0031] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods. Example 1
[0032] Weigh 2.0 g of LaAlO3 perovskite powder prepared by the sol-gel method and place it in a beaker. Separately weigh 1.18 g of boric acid (H3BO3, corresponding to a boron loading of approximately 37 wt%) and dissolve it in 20 mL of deionized water, stirring until completely dissolved. Slowly pour the boric acid solution into the beaker containing the LaAlO3 powder, and continuously stir in an 80 °C water bath until the water is completely evaporated, obtaining a homogeneous solid mixture. Dry the mixture at 120 °C for 12 hours, then transfer the dried solid mixture to a quartz boat and place it in a tube furnace. Under a nitrogen atmosphere (flow rate 50 mL / min), heat the mixture to 500 °C at a rate of 5 °C / min and maintain this temperature for 2 hours for heat treatment. After heat treatment, allow it to cool naturally to room temperature in a nitrogen stream, obtaining a white powdery solid, labeled 37B@LAO.
[0033] The morphology and microstructure of the obtained 37B@LAO catalyst were characterized using scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM). Figure 1 , 2 As shown, the obtained catalyst is composed of aggregates of particles with a particle size of approximately 50-200 nm. Figure 3 As shown in the HRTEM images, the crystalline LaAlO3 core is clearly encased in a weakly contrasting amorphous capping layer. Furthermore, observations of the freshly prepared catalyst (37B@LAO-Fresh) revealed an initial capping layer thickness of approximately 0.7 nm. Under propane oxidative dehydrogenation (ODHP) reaction conditions, this amorphous capping layer exhibited dynamic evolution: its thickness gradually increased with reaction time, reaching approximately 2.4 nm after 100 hours. This phenomenon directly confirms the formation of the core-shell structure and its dynamic stability during the reaction. Further electron energy loss spectroscopy (EELS) analysis showed that La and Al elements were mainly distributed within the particles, while B elements were highly enriched in the surface capping layer region, clearly distinguishable from the core region.
[0034] The chemical bonding state of the catalyst surface was analyzed using Fourier transform infrared spectroscopy (FT-IR). Figure 4 As shown, it is located at 1250-1420 cm. -1 The broad absorption bands within this range can be attributed to the stretching vibrations of the BO bond. More importantly, at approximately 1190 cm⁻¹... -1 and 885 cm -1 The characteristic absorption peaks appearing nearby, correlated with the stretching vibration mode of the Al-OB bond, indicate that the boron species are firmly anchored by bonding with metal sites on the perovskite surface. Meanwhile, the catalyst after the reaction exhibits a peak at 3200 cm⁻¹. -1The surrounding area still retains a distinct B-OH stretching vibration absorption band, indicating that the key hydroxyl species in the catalytic reaction are stably maintained. Example 2
[0035] The amount of boric acid was replaced with 0.36 g and 2.0 g respectively, and other operations were the same as in Example 1, to obtain boron loadings of 15% and 50% respectively. x The B@LAO samples were labeled as 15B@LAO and 50B@LAO, respectively.
[0036] The structure of the obtained catalyst was analyzed using X-ray diffraction (XRD). Figure 5 As shown, different boron loading amounts x The B@LAO samples all exhibited diffraction peak positions consistent with standard LaAlO3 (PDF 31-0022), indicating that the material maintains its perovskite crystalline phase under various conditions. Furthermore, changes in boron content did not lead to diffraction peak shifts or impurity phases, demonstrating that it forms a stable amorphous layer on the support surface without altering the main structure.
[0037] Application Examples: The catalyst prepared in the examples was tested for its catalytic performance in the propane oxidative dehydrogenation reaction. The reaction was carried out in an atmospheric pressure, single-stage temperature-controlled furnace, with the material loaded into a quartz tube reactor for testing. The specific operation is as follows: Filling: First, spread 30 mg of quartz wool in a quartz tube reactor with an inner diameter of 6 mm, a wall thickness of 2 mm, and a length of 360 mm. Then, select 200 mg of catalyst 37B@LAO prepared in Example 1 with a mesh size of 20-40 and fill it into the quartz tube reactor. Finally, spread another 20 mg of quartz wool on top of the material.
[0038] Column furnace heating conditions: Initial temperature 70℃, hold for 14 min, then increase to 120℃ at a rate of 20℃ / min and hold for 5 min to remove residual components from the chromatographic column.
[0039] Catalytic performance evaluation: The reaction was carried out with a feed gas of C3H8:O2:He = 6:3:11 (v / v / v), the gas flow rate was 20 mL / min, and the reaction temperature was 480-520℃.
[0040] Chromatographic analysis conditions: High-purity N2 was used as the carrier gas for both columns, with an FID flow rate and pressure of 0.04 MPa and a TCD flow rate and pressure of 0.2 MPa; hydrogen flow rates and pressures for FID1 and FID2 were 0.035 MPa and 0.03 MPa, respectively; the air flow rate and pressure were 0.03 MPa. Injector: 150 ℃; FID detector: 200 ℃; TCD detector: 200 ℃; Converter: 330 ℃.
[0041] Figure 6 A comparison of the catalytic performance of different catalysts prepared for the examples in the propane oxidative dehydrogenation reaction (reaction temperature 505℃). Figure 6 As shown, the 37B@LAO catalyst with an appropriate amount of boron species exhibits the best overall performance, achieving the highest propane conversion (approximately 33%) while significantly improving the selectivity of the target olefins; further increasing the boron loading (50B@LAO) can improve the selectivity of propylene, but it will significantly inhibit the overall conversion.
[0042] Figure 7 The catalytic performance of the 37B@LAO catalyst prepared in Example 1 in the propane oxidative dehydrogenation reaction at different temperatures is shown in the graph. Figure 7 As shown, this catalyst exhibits excellent propane oxidative dehydrogenation performance at temperatures ranging from 480 to 520 °C. Propylene is the main product, with its selectivity consistently remaining at a high level (approximately 70-90%), while ethylene and other byproducts account for a very low proportion. The CO and CO2 generated from deep oxidation are almost effectively suppressed. As the reaction temperature increases, the propane conversion rate increases from approximately 15% to approximately 45-50%, but the total olefin selectivity remains above 90%, demonstrating the catalyst's excellent selectivity control capability.
[0043] The stability of the 37B@LAO catalyst prepared in Example 1 during the oxidative dehydrogenation reaction at 500 °C was further investigated, and the results are as follows: Figure 8 As shown. By Figure 8 As can be seen, the 37B@LAO catalyst exhibits excellent ODHP performance at 500 °C. During the initial stage and long-term operation, its propane conversion remained stable at approximately 24%, propylene selectivity at approximately 81%, and the overall selectivity for olefin products such as ethylene and propylene consistently exceeded 97%. More importantly, during 100 hours of continuous operation, neither catalytic activity nor selectivity showed significant degradation, demonstrating excellent long-term operational stability.
[0044] In summary, the core-shell structured catalyst (37B@LAO) provided by this invention achieves a balance of high activity, high selectivity, and high stability in the propane ODHP reaction, effectively improving its ODHP reaction performance.
[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.
Claims
1. A core-shell perovskite catalyst containing an amorphous boron-oxygen layer, characterized in that, The core-shell perovskite catalyst consists of a crystalline perovskite support and an amorphous borate layer coating the surface of the support, wherein the amorphous borate layer is covalently bonded to the perovskite support.
2. The core-shell perovskite catalyst according to claim 1, characterized in that, The perovskite support is an ABO3 type perovskite, wherein A is selected from at least one of La, Sm, and Ce, and B is selected from at least one of Al, Co, Ni, Mn, and Fe.
3. The core-shell perovskite catalyst according to claim 1, characterized in that, The thickness of the amorphous borate layer is 0.5 nm to 5 nm.
4. The core-shell perovskite catalyst according to claim 1, characterized in that, Based on the total mass of the catalyst, the mass content of boron is 5% to 50%.
5. A method for preparing a core-shell perovskite catalyst as described in claim 1, characterized in that, Includes the following steps: (1) Preparation of perovskite support; (2) The perovskite support and the boron source were mixed to obtain a mixture; (3) The mixture obtained in step (2) is heat-treated to form an amorphous borate layer in situ on the surface of the carrier.
6. The method for preparing the core-shell perovskite catalyst according to claim 5, characterized in that, The boron source mentioned in step (2) is selected from at least one of boric acid, boron oxide, and borate esters.
7. The method for preparing the core-shell perovskite catalyst according to claim 5, characterized in that, The atmosphere for the heat treatment in step (3) is nitrogen, argon, or a mixture thereof.
8. The method for preparing the core-shell perovskite catalyst according to claim 5, characterized in that, The heat treatment in step (3) is performed at a temperature of 400 ℃ to 600 ℃ for 1 to 3 hours.
9. The application of a core-shell perovskite catalyst as described in claim 1 in the catalytic oxidative dehydrogenation reaction of alkanes, characterized in that, Propane is produced by oxidative dehydrogenation of propane using the core-shell structured perovskite catalyst.
10. The application according to claim 9, characterized in that, The temperature of the oxidative dehydrogenation reaction is 480 ℃~520 ℃, the reaction time is 0.5 h~2 h, and the volume ratio of C3H8 to O2 in the reaction feed gas is 1:1~3:1.